PENGELOLAAN DAN FAKTOR TIMBULAN LIMBAH BAHAN BERBAHAYA BERACUN (B3) DI PUSKESMAS CIPUTAT TIMUR - Anna Setiyani; Yeremiah Rubin Tjamin; Khoe Susanto Kusumahadi (Gunung Djati Conference Series, 2023)
Pollution of Dangerous Toxic Waste (LB3) is the problems which is considered dangerous because it is identified as having one or more chemical characteristics that are explosive, flammable, reactive, toxic, infectious, and corrosive. Puskesmas need consider relationship between health and the environment, because puskesmas are waste donors from their activities that are potentially hazardous. Therefore, it is necessary to manage LB3 correctly and safely in accordance with existing regulations for living things and it is surrounding circumstances and ensures health and safety workers and other people in the Puskesmas environment. This research is descriptive qualitative with the aim of knowing the LB3 management process carried out at Puskesmas which consists stages of sorting, storage and transportation as well as the generation factors of LB3 at Puskesmas. The method this research is interviews with officers who are directly responsible in LB3 handling and direct field observation. The research show LB3 management at sorting stage has met the requirements, at the storage stage some observations have met the requirements and there are still some that have not met the requirements, at the transportation stage they have met the requirements for the Environment and Forestry Ministry No. 06/2021 about Procedures to Requirements. Handling of Dangerous Toxic Waste and LB3 generation factors produced each month range from 0.03 - 0.17 kg/person.